2013
DOI: 10.1016/j.seizure.2013.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in a large cohort of children diagnosed with attention deficit/hyperactivity disorders (ADHD)

Abstract: The epilepsy diagnosis preceded the ADHD diagnosis, and was found in a significantly higher rate than would be expected in the general pediatric population. The majority of patients had mild epilepsy and ADHD-Combined Inattentive/Hyperactive-Impulsive Subtype. All cases with epilepsy and ADHD were treated with MPH, with initial response achieved in 86%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 40 publications
4
32
0
3
Order By: Relevance
“…Several epidemiological studies, with patient populations in the hundreds or thousands, indicate there may be a relationship between epilepsy and ADHD [108][109][110][111]. For instance, in a study using the Taiwanese health insurance database, epilepsy was found to be 3.94-fold more common in children and adolescents with ADHD (N = 3664) than in matched controls (N = 14,522), although the potential influence of ADHD medication upon seizures was not investigated [110].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies, with patient populations in the hundreds or thousands, indicate there may be a relationship between epilepsy and ADHD [108][109][110][111]. For instance, in a study using the Taiwanese health insurance database, epilepsy was found to be 3.94-fold more common in children and adolescents with ADHD (N = 3664) than in matched controls (N = 14,522), although the potential influence of ADHD medication upon seizures was not investigated [110].…”
Section: Introductionmentioning
confidence: 99%
“…48 Several researchers have supported this by reporting that ADHD, particularly the inattentive subtype, is often associated with epilepsy. 12,49 Identifying and managing attention deficit or ADHD in children with epilepsy is important for improving academic achievement and for formation and maintenance of interpersonal relationships. 50 Some limitations should be considered when interpreting our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It may be difficult to delineate ADHD symptoms from subtle seizures, especially in cases with inattentive subtype of ADHD which predominate in both epilepsy patients [2,15,31,32], and in patients with IED [7]. Another enigmatic association is that frequent IED (in more than 10% of the record) in the awake EEG can impair cognitive performance in children [33], and in some cases ADHD symptoms may be related to frequent epileptiform discharges activated by sleep as previously reported [34][35][36][37].…”
Section: Seizure Risk In Adhd Children With Ied and The Use Of Mph Anmentioning
confidence: 94%
“…We carried out a retrospective chart review of all patients aged 5-14 who were diagnosed with ADHD in accordance with DSM-IV TR [18]. For details see previous publications [7,15]. A digitized 20 min routine awake EEG with 21 electrodes (10-20 system) including hyperventilation and photic stimulation was performed.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation